Excimer emission based on the control of molecular structure and intermolecular interactions. Issue 14 (19th January 2016) - Lee, Jaehyun; Jung, Hyocheol; Shin, Hwangyu; Kim, Joonghan; Yokoyama, Daisuke; Nishimura, Hidetaka; Wakamiya, Atsushi; Park, Jongwook
Abstract : The wavelength of excimer formation and efficiency of an OLED device were controlled through the change of the center position of the triple-core chromophore. Abstract : Three triple-core chromophore derivatives based on anthracene and pyrene or chrysene moieties, 1, 6-bis-(10-[1, 1′;3′, 1′′]terphenyl-5′-yl-anthracen-9-yl)-pyrene (1, 6 DAP-TP ), 6, 12-bis-(10-[1, 1′;3′, 1′′]terphenyl-5′-yl-anthracen-9-yl)-chrysene (DAC-TP ), and 2, 7-bis-(10-[1, 1′;3′, 1′′]terphenyl-5′-yl-anthracen-9-yl)-pyrene (2, 7 DAP-TP ), were designed and synthesized. For1, 6 DAP-TP, anthracene was attached to the 1, 6 positions of pyrene. In the case ofDAC-TP, two anthracenes were connected to chrysene, located at the center position within the core, whereas in2, 7 DAP-TP anthracene was connected to the 2, 7 positions of pyrene. All three materials had highly twisted core structures and bulky m -terphenyl side groups introduced into the core. Excimer emission was observed in the solid film state and can be interpreted as the result of anisotropic intermolecular alignment (orientation effect). The wavelength of excimer formation was controlled through the change of the center position of the triple-core chromophore, and the color coordinate of white light and efficiency could be controlled when the materials were used in an electroluminescence (EL) device. Excimer EL emissions of1, 6 DAP-TP, DAC-TP, and2, 7 DAP-TP were at 591 nm, 556 nm, and 538 nm, respectively, and CIE coordinate values of the devices were (0.37, 0.31), (0.30, 0.37), and (0.32, 0.44), respectively, showing single molecular white emission.2, 7 DAP-TP showed a white OLED efficiency of 6.01 cd A −1 at 10 mA cm −2 .